Rapunzel's revenge - Hale, Shannon; Hale, Dean, 1972- (Bloomsbury, 2008)
A graphic novel that presents a comic twist on the classic tale of Rapunzel. In this version, Rapunzel uses her amazing braided hair as a whip or lasso as she travels with outlaw Jack in the wild West.